EFEKTIVITAS MEDIA CONGKLAK BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Harni Maulida.H; Meidy Soraya Sirajuddin; Nur Amaliah Mannang; Ulfa Alifiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low mathematics learning outcomes among elementary school students in Indonesia remain a persistent educational challenge, as reflected in national numeracy data consistently falling in the low category. One innovative approach considered promising is the use of local wisdom-based learning media, particularly the traditional game of congklak. Although several studies have examined congklak's effectiveness, a comprehensive systematic synthesis of findings has yet to be conducted. This study aims to analyze the effectiveness of local wisdom-based congklak media on elementary school students' mathematics learning outcomes through a Systematic Literature Review (SLR) approach. Articles were retrieved from Google Scholar, SINTA, and Garuda databases for the period 2019–2025 using the PRISMA 2020 guidelines. Of 20 articles identified, 15 met the inclusion criteria for in-depth analysis. Findings indicate that: (1) local wisdom-based congklak media consistently improves mathematics learning outcomes in whole number operations, GCD, LCM, and integers; (2) average improvement ranges from 15% to 40% compared to conventional instruction; and (3) congklak promotes active engagement, learning motivation, and conceptual understanding. This study concludes that local wisdom-based congklak is a viable mathematics learning medium in elementary schools and should be supported by teacher training and standardized implementation guidelines.